Att teoretisera om mening genom exempel: Vardagsspråkkritik, sam-vett och verklighetens svårighet - Löfgren, Ingeborg (Tidskrift för litteraturvetenskap, 2022)
Theorizing Meaning Through Examples: Ordinary Language Criticism, “Sam-vett” and the Difficulty of Reality In this article I set out to exemplify how one can, from within the tradition of Ordinary Language Criticism (OLC), theorize about literary meaning through concrete interpretative work. I proceed by attending to what I take to be a particular interpretive hard case, namely, the Swedish author and activist Sara Lidman’s (1923-2004) notion of “sam-vett”. Or more precisely: I attend to one specific usage of that word, namely the male protagonist Didrik Mårtensson’s usage of the word in Lidman’s novel Järnkronan (1985). Lidman invented the word “sam-vett” in the early 1980s but never defined it; she simply put it to use in various texts and contexts. By comparing how the problematic nature of “sam-vett” presents itself for Didrik in Järnkronan, with the Wittgensteinian philosopher Cora Diamond’s notion of “the difficulty of reality”, I argue that Lidman’s “sam-vett” – in this specific usage – expresses an experience of encountering something ineffable. In my comparative reading I argue that rather than offering a road to a more-than-human communality and knowledge beyond words, however, Didrik’s usage of “sam-vett” expresses a fantasy of being able to escape a guilty conscience through the letting go of sanity and sense-making altogether. So, while Didrik encounters “a difficulty of reality” that shoulders him out (at least partially) from language his attempt at imagining a non-linguistic pan-species community in the name of “sam-vett” nevertheless fails. Instead, Didrik’s “sam-vett” becomes something of a false idol, a delirious idea that only appears to make sense.